THE INFLUENCE OF MOTIVATION, DISCIPLINE AND COMPETENCE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN THE MANAGEMENT UNIT OF THE DKI PAVILION AND GRAHA WISATA TAMAN MINI INDONESIA INDAH - Jaenal Abidin; Sri Lestari Prasilowati (Jurnal Scientia, 2023)
DKI and Graha Wisata Taman Mini Indonesia Indah based on researchers observations, such as UP employees. Pavilion DKI and Graha Wisata Taman Mini Indonesia Indah currently feel less enthusiastic at work because of something that is not in accordance with expectations, This indicates that can b said that the expectations or demands of employees in achieving good work motivation have not been realized as they should, this reality cannot b allowed because such things can cause obstacles in achieving goals. The study was conducted at the DKI Pavilion Management Unit and Graha Wisata Taman Mini Indonesia Indah with a research population of 126 employees, the sample used was saturated sampling of 126 respondents, for data collection using questionnaire method techniques, and direct observation. And for data analysis using the Smart partial Least Square (PLS) analysis method version 3.0, for data tests used in this study are reliability tests, validity tests, statistical tests and classical assumptions tests. There is a direct positive and significant influence of motivation on employees performance. There is a direct positive and significant influences of motivation on Job Satisfaction. Work discipline has a direct positive and significant influences on employees performance. Work discipline has a direct positive and significant influences on job satisfaction. There is a direct positive and significant influences of Competency on employees performance.